Determination of the Non-Market Values of Functions and Services of the National Park Kiasar - Sareh Hosseini; Hamid Amirnejad; Jafar Oladi (فصلنامه پژوهش‌های اقتصادی ایران, 2017)
National park is one of the world's natural ecosystems and the most vital environment for sustainable development of the environment and the ecological phenomenon whose valuation of their functions and services is one of the most effective factors in their stability. In order to achieve this goal, ecological and socioeconomic functions and services of Kiasar national park in northern Iran which include two forest and rangeland ecosystems using direct market methods, benefits transfer, cost-based methods and the replacement cost has been valued. In this research, the economic value of forest and rangeland ecosystem of Kiasar national park in 1393 was determined to be 2132.59 and 61.47 billion Rials, respectively. Based on the results, the total economic value of the services and functions of Kiasar national park is 883.2 billion Rials and the economic value per hectare is estimated at 388.59 million Rials. Also, three functions, water conservation, natural gas regulation and habitat have the highest share and two land and social functions have the lowest share of the economic value of the Kiasar national park. These results suggest that the national park Kiasar in terms of ecology more than the economic and social aspects.